Analysis of Determinants of Agribusiness investment in a Young Economy: Nigeria (1999 -2008) - O., Nto Philip (Journal of Social and Development Sciences, 2011)
The study examined determinants of agribusiness investment in Nigeria. Data for the study are time series collected on quarterly basis from publications of Central Bank of Nigeria (CBN), National Bureau of Statistics (NBS) and National Population Commission (NPC). Some firms’ specific data were collected from published and unpublished records of forty (40) agribusiness enterprises randomly selected in Nigeria. Vector Auto Regression (VAR) model was used to analyze the data. Among the determinants of agribusiness investment in Nigeria analyzed by the study, tax paid, market size and exchange rate were found to be statistically significant at 5% probability level. Based on the results, it was recommended that government should enforce the policy on five-year tax holiday for young agribusiness firms and also establish Agribusiness Investment Protection Agency which will be charged with the responsibility of liaising with other relevant agencies to create enabling environment for agribusiness firms.